Decreases in colonic and systemic inflammation in chronic HIV infection after IL-7 administration. - Irini Sereti (Public Library of Science (PLoS), 2014)
Despite antiretroviral therapy (ART), some HIV-infected persons maintain lower than normal CD4(+) T-cell counts in peripheral blood and in the gut mucosa. This incomplete immune restoration is associated with higher levels of immune activation manifested by high systemic levels of biomarkers, including sCD14 and D-dimer, that are independent predictors of morbidity and mortality in HIV infection. In this 12-week, single-arm, open-label study, we tested the efficacy of IL-7 adjunctive therapy on T-cell reconstitution in peripheral blood and gut mucosa in 23 ART suppressed HIV-infected patients with incomplete CD4(+) T-cell recovery, using one cycle (consisting of three subcutaneous injections) of recombinant human IL-7 (r-hIL-7) at 20 µg/kg. IL-7 administration led to increases of both CD4(+) and CD8(+) T-cells in peripheral blood, and importantly an expansion of T-cells expressing the gut homing integrin α4β7. Participants who underwent rectosigmoid biopsies at study baseline and after treatment had T-cell increases in the gut mucosa measured by both flow cytometry and immunohistochemistry. IL-7 therapy also resulted in apparent improvement in gut barrier integrity as measured by decreased neutrophil infiltration in the rectosigmoid lamina propria 12 weeks after IL-7 administration. This was also accompanied by decreased TNF and increased FOXP3 expression in the lamina propria. Plasma levels of sCD14 and D-dimer, indicative of systemic inflammation, decreased after r-hIL-7. Increases of colonic mucosal T-cells correlated strongly with the decreased systemic levels of sCD14, the LPS coreceptor - a marker of monocyte activation. Furthermore, the proportion of inflammatory monocytes expressing CCR2 was decreased, as was the basal IL-1β production of peripheral blood monocytes. These data suggest that administration of r-hIL-7 improves the gut mucosal abnormalities of chronic HIV infection and attenuates the systemic inflammatory and coagulation abnormalities that have been linked to it.